1984
DOI: 10.1007/bf01868529
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of intracellular calcium in the phosphate efflux from mammalian nonmyelinated nerve fibers

Abstract: Phosphate efflux was measured as the fractional rate of loss of radioactivity from desheathed rabbit vagus nerves after loading with radiophosphate . The effects of strategies designed to increase intracellular calcium were investigated. At the same time, the exchangeable calcium content was measured using 45Ca. Application of calcium ionophore A23187 increased phosphate efflux in the presence of external calcium in parallel with an increase in calcium content. In the absence of external calcium, there was onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It has been shown in squid axon that lack of external Na produces a large increase in Ca inflow through the Cao/Nai exchange, which is very dependent on the Na content of the axon (Baker & DiPolo, 1984). Furthermore, in a previous paper we have shown that omission of Nao produces an increase in phosphate efflux, which probably also reflects an increase in the rate of the Cao/ Nai exchange Jirounek et al, 1984).…”
Section: Effect Of External Namentioning
confidence: 96%
“…It has been shown in squid axon that lack of external Na produces a large increase in Ca inflow through the Cao/Nai exchange, which is very dependent on the Na content of the axon (Baker & DiPolo, 1984). Furthermore, in a previous paper we have shown that omission of Nao produces an increase in phosphate efflux, which probably also reflects an increase in the rate of the Cao/ Nai exchange Jirounek et al, 1984).…”
Section: Effect Of External Namentioning
confidence: 96%
“…This type of Pi transport has been studied most extensively in kidney and intestine, where it is responsible for the rate-limiting step in transepithelial Pi transport. Studies have now been initiated on P~ transport processes in heart and skeletal muscle (Nuutinen & Hassinen, 1981;Medina & Illingsworth, 1980), nerve fibers (Jirounek et al, 1982(Jirounek et al, , 1984, across the placenta (Stulc & Stulcova, 1984;Brunette & Allard, 1985), and in a variety of cultured cell lines. In addition, uptake of P~ by cancer cells has been studied (Wehrle & Pedersen, 1982;Bowen & Levinson, 1983), partly to determine whether Pi uptake plays a role in rapid growth.…”
Section: H+/pi Cotransport In Higher Plants Appears To Include a Highmentioning
confidence: 99%
“…The characteristics and molecular identity of the P i efflux system in various cells have not been well established. A few reports have examined the P i efflux system in opossum kidney (OK) cells (1), pancreatic islets (11,12), and vagus nerves (19). In the proximal tubule, the way in which P i exits from the basolateral side is not well defined.…”
mentioning
confidence: 99%